Tradisi lisan, naskah, dan sejarah; Sebuah catatan politik kebudayaan - Duija, I Nengah (UI Scholars Hub, 2005)
Tradition can be seen from two different perspectives, those of literacy (writing system) and of oral tradition. Recently, some intellectuals have shown interest in oral tradition as academic study in some universities. Oral tradition is not supposed to be seen merely as part of the past and a cultural entity of no importance. This paper describes the two traditions of oral literature and manuscript writing as a basis for local historical knowledge and records of cultural politics. The discussion will be more about the content of tradition that is related to the history of cultural politics than a historical observation.